Adaptation biology and medicine cell adaptations and challenges - Wang, P. (Narosa, 2011)
In broad terms, the present day existence of all forms of life on earth is the result of adaptation by organisms over time to the given environment/circumstance. More recently, it has also been seen that a gradual adaptation to repeat exposures to different stresses such as hypoxia, heat, cold, infections, exercise, etc. increases the resistance of the organisms not only to each of these stresses, but also to other potentially harmful conditions. An understanding of the science behind the process of such an adaptation is the key to future therapies. Several chapters in this book cover new developments in our understanding of the biology of adaptation at the molecular, cellular, organ and whole body level. Some of the chapters also consider translational aspects of such a knowledge. This book will be of great value to experimental biologists as well as clinicians who deal with a wide variety of disease conditions.